2001
DOI: 10.1017/s0022112001003950
|View full text |Cite
|
Sign up to set email alerts
|

Segregation patterns in gas-fluidized systems

Abstract: The formation of segregation patterns in initially homogeneous, fluidized, binary mixtures of particles has been studied. The adjustment of the bed depends on the proportions of fine and coarse particles in the mixture and the gas flow rate relative to the minimum fluidization velocities of the two components. The particles are immobile until the gas flow rate is sufficiently large to fluidize the mixture of particles. When the gas flow rate exceeds this critical value, alternating vertical bands of coarse and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 9 publications
2
21
0
Order By: Relevance
“…Fluidisation of granular flows can also enhance segregation of large particles to flow perimeters (e.g. Gilbertson and Eames, 2001), thus increasing permeability in the flow borders and making it possible to develop similar instabilities which owe their formation to the dry frictional perimeter that surrounds a partly fluidised interior.…”
Section: Insights From Laboratory Experiments and Numerical Simulationsmentioning
confidence: 99%
“…Fluidisation of granular flows can also enhance segregation of large particles to flow perimeters (e.g. Gilbertson and Eames, 2001), thus increasing permeability in the flow borders and making it possible to develop similar instabilities which owe their formation to the dry frictional perimeter that surrounds a partly fluidised interior.…”
Section: Insights From Laboratory Experiments and Numerical Simulationsmentioning
confidence: 99%
“…6. Gilbertson and Eames (2001) suggested that the particles are immobile until K h exceeds K f . At this point fluidisation occurs and alternating vertical bands of coarse and fine particles form.…”
Section: Fluidisationmentioning
confidence: 99%
“…The rate of segregation was very often measured by the bed freeze and dissection method, where the particles are taken from the fluidised bed layer by layer and sieved separately to measure the concentrations of the different species (Wu and Baeyens, 1998;Marzocchella et al, 2000;Formisani et al, 2001;Gilbertson and Eames, 2001). A disadvantage of this method is that it is very laborious and the results suffer from significant inaccuracies.…”
Section: Introductionmentioning
confidence: 99%